In vitro estimation of superfluid critical extracts of some plants for their antimicrobial potential, phytochemistry, and GC-MS analyses - Waleed Bakry Suleiman (BMC, 2020)
Abstract Background Along with swift economic evolution and continuous amelioration of lifestyle, people at present are paying more attention to health issues. Synthetic drugs will be compensated with other natural ones that belong to natural origin. Plants have always been considered as sources of several compounds that are used in many fields, especially human and animal health, starting from boosting immunity to the treatment of infectious diseases caused by some pathogenic microbes such as bacteria, fungi as well as viruses. This study aimed to incorporate some types of plants within the antimicrobial portfolio through the examination of different six plants which were Cichorium intybus, Cinnamomum camphora, Commiphora myrrha, Foeniculum vulgare, Nerium oleander, and Spartium junceum. As well, attempting to identify the active constituents of their extracts using GC-MS. Materials and methods All selected plants were analyzed to determine their phytochemical composition such as phenolics, alkaloids, flavonoids, terpenoids, and so on. The extraction step was done by sophisticated equipment called supercritical fluid extractor SFE through adjustment of specific conditions include temperature, time, flow rate and pressure to change the behavior of CO2. Testing the antimicrobial activity of each plant extract via agar well diffusion method through the formation of clear zones against a wide range of test microorganisms including both Gram-positive and Gram-negative bacteria as well as yeasts. Finally, attempting to primarily identify the constituents of each plant extract using GC-MS. Results and discussion The crude extract of F. vulgare showed the highest potency against C. albicans, E. faecalis and S. typhimurium, it contains some unique compounds such as squalene, eugenol and isoeugenol while, Extract of C. intybus showed a moderate activity especially against C. lipolytica and MRSA and it includes Vitamin A like compound which indicates antioxidant property. Conclusion Conclusively, fennel gave a promising result as a good wide spectrum antimicrobial agent because it contains some compounds act as antimicrobial agents such as eugenol which was used as food preservatives in addition to squalene which acts as an antioxidant and antimycotic agent so, it will be useful especially while it was used in highly purified form excluding all undesirable subcomponents.